Phytochemical Profiling, Antibacterial Properties and Toxicity of Amla Fruit Tea (Phyllanthus emblica L.): An In Vitro and In Silico Study - Cahyaningrum, Putu Lakustini; Sudaryati, Ni Luh Gede; Bogoriani, Ni Wayan; Asih, Ida Ayu Raka Astiti; Adnyana, I Made Dwi Mertha; Jenar, Putut Dewantha (Journal of Multidisciplinary Applied Natural Science, 2025)
Antimicrobial resistance represents a critical global health challenge, necessitating the exploration of alternative therapeutic agents. This study investigated the antimicrobial potential of amla fruit tea (Phyllanthus emblica L.) through comprehensive phytochemical characterization, antibacterial assessment, and computational modeling to identify potential mechanisms of action. LC-HRMS analysis was employed for phytochemical profiling, antibacterial activity was evaluated via disk diffusion method against Staphylococcus aureus and Escherichia coli, and molecular docking studies were conducted against tyrosyl-tRNA synthetase and FimH adhesin proteins. Analysis identified 89 bioactive compounds, with oxidized hydroxytetrahydrofuranyl acetate, L-α-palmitin, and ellagic acid predominating. Antibacterial activity against S. aureus and E. coli was evaluated via the disk diffusion method, revealing that moderate inhibition increased at higher concentrations (25%) and with extended exposure, with E. coli exhibiting greater susceptibility than S. aureus. Molecular docking studies against tyrosyl-tRNA synthetase (S. aureus) and FimH adhesin protein (E. coli) identified the W-18 benzenesulfonamide derivative as the most promising compound, which demonstrated strong binding affinities of -11.01 and -7.48 kcal/mol, respectively. While all five principal compounds met Lipinski's drug-likeness criteria, toxicological assessment revealed varying safety profiles, with two compounds classified as "possibly hazardous" and two as "toxic when swallowed." These findings suggest that amla fruit tea has antibacterial properties through two mechanisms: disruption of protein synthesis and bacterial adhesion. However, its efficacy remains considerably lower than that of conventional antibiotics, suggesting potential applications as complementary therapy rather than antibiotic replacement.